Perancangan Interior Cafe Salon Di Malang - Djuari, Celia Magaski (Intra, 2015)
Malang City has good prospect in the culinary fields such as cafes and salon, because the consumptive lifestyle as become a trend in Malang City. CafeÂ is often used as a place to gather and meet the culinary needs, while salon is often used as a place to let saturation off and body pampering. These perspectives brings Malang into a need of a space to fulfill consumer consumptive pattern and to release saturation in Malang City. This design uses the concept of